Return mapping algorithm for an enhanced generalized plasticity constitutive model of partially saturated soils - Zhang, H.W.; Santagiuliana, R.; Schrefler, B.A. (Computers and geotechnics, 2012)
The objective of this paper is to investigate the stress update algorithm and the tangent operator for an enhanced generalized plasticity model developed recently for partially saturated soils, where on top of the hydrostatic and deviatoric components of the (effective) stress tensor suction has to be considered as an independent variable. The soil model used for the applications can be derived from a potential energy function and is thermodynamically consistent. The Galerkin method is used to obtain a weak form of the governing equations and a “stress–suction coupling matrix” is derived in the discretization in space by finite element method. The implicit integration algorithm is incorporated in a code for partially saturated soil dynamics. The framework of generalized plasticity is presented and examples are shown including subsidence above a model gas reservoir.